X-Ray Computer Tomograhy - Potential and Limitation for the Measurement of Local Solids Distribution in Circulating Fluidized Beds - Wirth, Karl-Ernst; Graßler, Thomas (1st World Congress on Industrial Process Tomography, 1999)
The characterization of the gas-solids flow inside a circulating fluidized bed, especially the knowledge about the solids distribution in the vertical tubes, is the basis for a optimum reactor design as well as for finding suitable operating con- ditions and for modeling the multiphase flow inside the reactor. To determine data of solids concentration with high spatial resolution an x-ray computer tomography system is used. This system mainly consists of a 60 keV x-ray source and an x-ray linear detector with 1024 sensitive elements, which gives 8 bit-values representing integral solids concentrations between the x-ray source and the detector. A number of experiments have been carried out both at the upflow and at the downflow of two different circulating fluidized beds containing glass beads of 70 μm at superficial gas velocities from 2 to 7 m/s. Results show that the x-ray computer tomography system is applicable to average solids concentrations from 1 up to 20 Vol-% of solids concentration in a tube with 0.19 m inner diameter.
UnivIS-Import:2015-04-16:Pub.1999.tech.ITC.mechve.xrayco_94
Keywords: X-ray; Computer tomography; Circulating fluidized bed; Multiphase flow